Pollinator activity and flowering in agricultural weeds in Sweden - Per Milberg; Markus Franzen; Amanda Karpaty Wickbom; Sabine Svelander; Victor Johansson (Ecology and Evolution, 2024)
Abstract The extent to which weeds in arable land are useful to pollinators depends in part on the temporal pattern of flowering and insect flight activity. We compiled citizen science data on 54 bees and hoverflies typical of agricultural areas in southern Sweden, as well as 24 flowering weed species classified as pollinator‐friendly in the sense that they provide nectar and/or pollen to pollinators. The flight periods of the bees and hoverflies varied greatly, but there were also some consistent differences between the four groups studied. The first group to fly were the early flying solitary bees (7 species), followed by the social bees (18 species). In contrast, other solitary bees (11 species) and hoverflies (22 species) flew later in the summer. Solitary bees had the shortest flight periods, while social bees and hoverflies had longer flight periods. Flowering of weed species also varied greatly between species, with weeds classified as winter annuals (e.g., germinating in autumn) starting early together with germination generalists (species that can germinate in both autumn and spring). Summer annuals (spring germinators) and perennials started flowering about a month later. Germination generalists had a much longer flowering period than the others. Weekly pollinator records were in most cases significantly explained by weed records. Apart from early flying solitary bees, all models showed strong positive relationships. The overall best explanatory variable was the total number of weeds, with a weight assigned to each species based on its potential as a nectar/pollen source. This suggests that agricultural weeds in Sweden provide a continuous potential supply of nectar and pollen throughout the flight season of most pollinators.